The Effectiveness Of Tera Exercise And Yoga Exercise On Blood Pressure Changes In Hypertensive Elderly At Panti Werdha Santo Yoseph - Nurul Diah Rahmatani; Joko Sutrisno (Journal of Health Science Community, 2025)
Hypertension in the elderly increases the risk of serious complications. Tera exercise and yoga exercise are non-pharmacological interventions that can help lower blood pressure. This study aims to analyze the effectiveness of Tera exercise and yoga exercise in reducing blood pressure among hypertensive elderly at Panti Nursing Home Santo Yoseph, Kediri City. This quantitative study employed a two-group pretest-posttest design. A total of 30 elderly individuals with hypertension at Panti Wredha Santo Yoseph, Kediri City, were divided into two groups: 15 participants in the Tera group and 15 participants in the Yoga group. The intervention was conducted over four sessions within one month, with a frequency of once per week. Data were analyzed using the Wilcoxon test and the Mann-Whitney test. The study results showed that before the intervention, 8 participants (53.3%) in tera exercise and 7 participants (46.7%) in yoga exercise had blood pressure in the mild hypertension category. After the intervention, 6 participants (40%) in both types of exercise experienced a decrease in blood pressure to the normal category. The results of the Wilcoxon test showed a significant difference in blood pressure before and after the intervention in the Tera Gymnastics group, with a p-value of 0.001 for systolic and 0.001 for diastolic blood pressure. Similarly, in the Yoga Exercise group, significant differences were observed, with a p-value of 0.011 for systolic pressure and 0.012 for diastolic pressure, indicating that Yoga Exercise effectively reduced blood pressure in hypertensive elderly individuals. The Mann-Whitney test results indicated that the post-test systolic blood pressure significance value between the Tera Exercise and Yoga Exercise groups was 0.771, while the post-test diastolic blood pressure significance value was 0.983 (p > 0.05). These findings suggest no significant difference between the two groups in lowering blood pressure. There is no significant difference in the effectiveness of Tera Exercise and Yoga Exercise in reducing blood pressure among hypertensive elderly individuals at Panti Werdha Santo Yoseph, Kediri City.